Anti‐interleukin 5 antibody is effective for not only severe asthma and eosinophilic pneumonia but also eosinophilic bronchiolitis. Issue 2 (18th December 2018) - Tomyo, Fuminori; Sugimoto, Naoya; Kawamoto, Masashi; Nagase, Hiroyuki; Yamaguchi, Masao; Ohta, Ken
Abstract : A 60‐year‐old female with severe bronchial asthma developed persistent dyspnoea and an abnormal lung shadow. High‐resolution computed tomography (HRCT) demonstrated patchy ground‐glass opacities and diffuse, small nodular shadows. Elevated percentages of eosinophils were observed in the blood and bronchoalveolar lavage fluid. These results collectively indicated that her asthma was accompanied by eosinophilic pneumonia and eosinophilic bronchiolitis. Although previous, rare case reports suggest that systemic steroid therapy is necessary and effective for the control of eosinophilic bronchiolitis, we chose to treat her with an anti‐interleukin 5 antibody, mepolizumab. Her asthma, eosinophilic pneumonia, and eosinophilic bronchiolitis each improved in response to mepolizumab as assessed from her symptoms, pulmonary function tests, and HRCT. Mepolizumab might be effective not only for asthma and eosinophilic pneumonia but also for eosinophilic bronchiolitis. Abstract : There have been a few case reports of eosinophilic bronchiolitis that is characterized by radiographic findings showing diffuse bronchiolitis plus massive accumulation of eosinophils in the airways. Systemic steroid therapy has been suggested to be effective for this disorder, although the precise pathogenesis in unknown. Here, we report a case of severe asthma complicated with eosinophilic pneumonia and eosinophilic bronchiolitis, all of which were alleviated by anti‐interleukin 5 (IL‐5) antibody.